2009
DOI: 10.3109/09638280903349545
|View full text |Cite
|
Sign up to set email alerts
|

Health-related and subjective quality of life of older adults with visual impairment

Abstract: HRQOL of older adults with VI is mainly explained by level of participation correlates, while their SQOL is mainly explained by depressive symptoms and satisfaction variables. The results also underscore the importance of social roles for HRQOL and SQOL of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 53 publications
3
41
0
4
Order By: Relevance
“…Nevertheless, satisfaction with participation in social roles was previously found to best predict QOL [17,22]. Considering both accomplishment level and satisfaction with social participation, these studies did not find that accomplishment level of participation in social roles best predicts QOL when considering satisfaction with social participation.…”
Section: Associations Between Quality Of Life and Accomplishment Levementioning
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, satisfaction with participation in social roles was previously found to best predict QOL [17,22]. Considering both accomplishment level and satisfaction with social participation, these studies did not find that accomplishment level of participation in social roles best predicts QOL when considering satisfaction with social participation.…”
Section: Associations Between Quality Of Life and Accomplishment Levementioning
confidence: 82%
“…Conducted with individuals with traumatic brain injury, this study found that QOL was strongly correlated with satisfaction with social participation (subjective) but not with accomplishment level of social participation (objective). Based on this study, the conceptualization of QOL [20,21], and results from three exploratory studies [16,17,22], it can be hypothesized that QOL of older adults should be more associated with satisfaction with social participation than with accomplishment level of social participation. Moreover, to our knowledge, no study aimed at identifying the correlates of satisfaction with social participation.…”
Section: Introductionmentioning
confidence: 99%
“…However, as these adults were not in an acute state, they may have already adapted to their living conditions and, as a result of resilience, flexibility and coping skills they may have the impact of the disabling condition they are experiencing on their own QoL [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Old persons generally have a positive outlook on life despite their sensory loss: they tend, for instance, to believe that visual loss is expected in later life and often ignore disturbances which impact worsening vision [9]. Additionally, as a result of resilience, of accumulated flexibility and coping skills in dealing with everyday problems, they report a life satisfaction higher than younger age cohorts with visual impairment or older sighted cohorts [10,11]. Research studies seem, then, to support the idea of a non specific role of aging on quality of life (QoL) perceived by old persons with visual impairment and encourage the investigation of the potential role of other dimensions, at the same time paying attention to both the physical and mental status and daily functioning, and problem solving and to their relationship with perceived QoL.…”
Section: Introductionmentioning
confidence: 99%
“…A deficiência visual e a qualidade de vida estão associadas diretamente ao convívio social, em que relacionar-se e ter amigos implicará em uma melhor qualidade de vida. Isto evidenciado em estudos com idosos chineses (WANG et al, 2008;ZHANG et al, 2012) e canadenses (RENAUD et al, 2010). Entendemos a importância destes espaços de trocas e interações entre pares, no caso pessoas com deficiência visual, no sentido de que há uma sintonia entre as realidades vividas e uma produção de significado concreto para com a realidade falada com sua própria experiência.…”
Section: Motivação à Prática De Atividade Físicaunclassified